2010
DOI: 10.1038/oby.2009.444
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of PTP1B by Trodusquemine (MSI‐1436) Causes Fat‐specific Weight Loss in Diet‐induced Obese Mice

Abstract: Trodusquemine (MSI-1436) causes rapid and reversible weight loss in genetic models of obesity. To better predict the potential effects of trodusquemine in the clinic, we investigated the effects of trodusquemine treatment in a murine model of diet-induced obesity (DIO). Trodusquemine suppressed appetite, reduced body weight (BW) in a fat-specific manner, and improved plasma insulin and leptin levels in mice. Screening assays revealed that trodusquemine selectively inhibited protein-tyrosine phosphatase 1B (PTP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
134
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(155 citation statements)
references
References 38 publications
(62 reference statements)
11
134
0
Order By: Relevance
“…2D), highlighting a potential role of PTP1B in restraining ovarian tumor cell function. Consistent with these findings, we observed the opposite effects of treatment of both HOSE cell lines with a specific, small molecule inhibitor of PTP1B, MSI-1436 (17,18). Cell proliferation, which was monitored by BrdU incorporation (Fig.…”
Section: Ptp1b Was Down-regulated In Ovarian Carcinoma-derivedsupporting
confidence: 73%
See 2 more Smart Citations
“…2D), highlighting a potential role of PTP1B in restraining ovarian tumor cell function. Consistent with these findings, we observed the opposite effects of treatment of both HOSE cell lines with a specific, small molecule inhibitor of PTP1B, MSI-1436 (17,18). Cell proliferation, which was monitored by BrdU incorporation (Fig.…”
Section: Ptp1b Was Down-regulated In Ovarian Carcinoma-derivedsupporting
confidence: 73%
“…When we overexpressed PTP1B in the cancer cell lines, to the levels detected in normal epithelial cells, it resulted in impaired cell invasion and migration, delayed proliferation, and increased cell death through apoptosis. Conversely, we observed that treatment of the normal ovarian surface epithelial cells with a small molecule inhibitor of PTP1B (17,18) led to enhanced proliferation and motility. These data are consistent with a role for PTP1B in attenuating signals that are important for the tumor phenotype.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Currently, trodusquemine (Fig. 1), a selective PTP1B inhibitor, has reached phase 1 clinical trials and shows interesting preclinical results as antidiabetic agent and appetite suppressant [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, most molecules have proven difficult to develop into drugs due to the large weight (>500Da), high negative charges, low cell permeability and poor bioavailability. Up to now, there are only two small molecules proceeding to clinical research phase, MIS-1436 entering into phase I clinical trials [4] and ISIS113718 entering into phase clinical trials [5]. Therefore, it is still important to develop new drugs targeting PTP1B for the treatment of diabetes and obesity.…”
Section: Introductionmentioning
confidence: 99%